The effect of bound calorific value and burning rate on biobriquettes from salak skin with starch adhesive - Alexander, Irving Josafat; Silaban, Ramlan; Sirait, Gloria (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Massive technological development is something that cannot be avoided in this life, because technological development is in line with scientific progress. Indonesia is a country that has abundant energy of various kinds source. Currently, energy use in Indonesia still comes from oil and gas earth, as well as coal which is non-renewable resources. Dependence on energy becomes main problem in energy supply national. Considering the need for it fuel every year continues has increased and is necessary anticipation of the availability of energy sources which is getting thinner while the price fuel oil increases. Every country in the world is now focusing on energy production through non-conventional sources. Biomass is an alternative energy source to replace fossil fuels (oil earth) because it has several beneficial properties, including being able to be utilized economically sustainable because of its renewable nature, no contains sulfur so the biomass does not cause air pollution. Besides being able to reduce waste, if managed properly biomass has high potential to be used as an alternative energy source in the form of biobriquettes. The method used in this research includes the preparation of salak skin raw materials, the carbonisation stage of salak skin, the starch adhesive preparation stage and the salak skin analysis stage, namely the analysis of calorific value and burning rate. Based on the results of the calorific value analysis and combustion rate analysis, it can be concluded that the biobriquette sample of salak skin with starch adhesive has met the provisions of the SNI No. 01-6235-2000 on charcoal biobriquettes. From the results of the study, it was also found that the Biobriket B sample, namely by using adhesive, has a high calorific value and burning rate compared to Biobriket A, namely without using adhesive.